Frequency of Blood Eosinophilia in Patients of Acute Exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) - Sehar Saba Samuel, Bushra Batool, Samiullah, Mohammad Mohsin Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of eosinophilia in patients presenting with acute exacerbation chronic obstructive pulmonary disease (AECOPD). Patients and Methods: A total number 217 patients presenting with AECOPD were included from August-2021 to March-2022. Data regarding patients age, gender, diabetes, hypertension, smoking and duration of COPD was collected for each patient. After inclusion, venous blood samples were taken and were analyzed for presence of eosinophilia. Results: Mean age of patients was 59.32±8.92 years. Mean duration of COPD was 6.56±2.49 years. There were 127 (74.7%) male and 43 (25.3%) female patients. Out of 170, 121 (71.2%) patients were smokers, 66 (38.8%) diabetic and 79 (46.5%) hypertensive patients. Eosinophilia was diagnosed in 37 (21.8%) patients. Conclusion: Based on the data of our study including 170 patients hospitalized for AECOPD, we found that 21.8% patients had blood eosinophilia (defined as ≥300 cells/μL). So Peripheral blood eosinophilia can be used a significant biomarker in patients with acute exacerbation of COPD.